A desert songbird with no confamilials in the Western Hemisphere (Verdin, Auriparus flaviceps) investigates divergent conspecific songs. Issue 3 (8th May 2021) - Greig, Emma I; Kinnebrew, Eva; Witynski, Max L; Larsen, Eric C
Abstract: Most birds that show geographic variation in their songs discriminate between local and foreign songs, which may help them avoid unnecessary conflicts with vagrant individuals or similar-sounding congeners. However, some species respond equally to foreign and local songs, which may be useful if foreign individuals present territorial threats or if there are no sympatric congeners to avoid. Species without sympatric congeners are not commonly tested in playback studies, but they offer an opportunity to see how song variation and recognition unfolds when the pressure to avoid similar congeners is absent. Here, we use Verdins ( Auriparus flaviceps ), a monotypic genus of songbird with no confamilials in North America, to explore song variation and recognition in a species living without close relatives. We assessed geographic variation in song across the Verdin range and conducted a playback experiment using exemplars from 2 acoustically divergent and geographically distant regions as treatments. We found significant geographic variation in song that mapped well onto ecologically distinct desert regions. We found that Verdins had stronger vocal responses to local-sounding songs, but had equal movement responses to local-sounding and foreign songs. These results are similar to results found in other species without sympatric congeners and provide an example of a species that investigates acoustically divergent conspecific songs, despite recognizing salient differences in those songs. Graphical Abstract: Lay Summary: Many songbirds have geographic variation in their songs. Most species prefer songs that sound local, or familiar, but some will respond to foreign songs just as readily as they respond to local songs. This may be more likely if there are no similar-sounding relatives around, and therefore no risk of mistaken identity. Few species without close relatives have been studied, so we study one that is also a desert specialist, the Verdin ( Auriparus flaviceps ). We found that Verdins have geographic variation in song that mapped well onto large desert habitat regions, and they sing less to playbacks of songs from distant regions. However, despite recognizing salient differences in foreign songs, they are just as likely to approach foreign songs as local-sounding songs, as are other species that live without close relatives. When close relatives are absent, birds may be more permissive in what they consider a song worth investigating.